Multi-Frame Digital Interferometry Using a Single Digital Record System [Interferometría Digital Multicuadro Usando Un Único Sistema de Registro Digital] - Watkins-Orellana, F; Castro-Barrera, M; Pedreros, J (Institute of Electrical and Electronics Engineers Inc., 2016)
In this work a multi-frame interferometric system based in digital image processing and digital interferometry is presented. Here, an experimental optical setup which integrates the virtues of the digital interferometry technique and the capacity to capture two interferograms, to two different times, in a single digital recording system is implemented. The digital reconstruction of the interferograms required the capture of three interferometric patterns of very thin parallel fringes (15-20 lines/mm), one of them with information of the phase object and the other two are interferometric patterns of reference. One of the referential pattern is captured in the same condition as the one with plasma and the other one slightly changing the frequency of the pattern fringes. The interferogram associated with each instant of time is separated by means of spatial filtering techniques. Thus, the technique allows obtain digital interferograms in fringes of infinite and finite width in two different times. The interferometric system was tested in a laser-induced spark plasma in air. © 2016 IEEE.